Privatization as a means to societal transformation: An empirical study of privatization in Central and Eastern Europe and the Former Soviet Union - Nichole M. Castater (Fondazione Eni Enrico Mattei (FEEM), 2002)
There have been numerous empirical studies of privatization programs, which have found efficiency gains to firms, industries, and financial markets in a multitude of developed and developing economies. Central and Eastern Europe and the Former Soviet Union are conspicuously and consistently absent from these studies. Some reasons for this include the lack of reliable and consistent firm data both before and after privatization, the absence of vital business mechanisms and institutions to distribute reliable business information, and misconceptions about what privatization actually is. Given these problems, Stiglitz (1998) offers an interesting solution for measuring the "success" privatization in CEE and FSU. Stiglitz (1998) provides six factors to be considered when assessing the impact of any type of economic reform: economic growth, health, education, infrastructure, knowledge, and capacity-building. Through correlation analysis, financial, economic and social variables representing these six dimensions are reduced to fourteen key variables that describe privatization / economic reform success.A series of mean analyses are performed, taking into consideration privatization program characteristics and control variables to account for other economic reforms that have occurred simultaneously with privatization. General findings suggest that overall there is positive economic, financial, and social growth after privatization. However, it is difficult to discern the effects of privatization, from the effects of other economic reforms. In addition, countries that have manager/employee privatization do not have sale privatization as part of their programs experience negative growth in market capitalization, value of stocks traded, and official development assistance.
Keywords: 330; Privatisierung; Wirkungsanalyse; Wirtschaftsindikator; Sozialer Indikator; Osteuropa; GUS-Staaten